Analisis Pengaruh Mouth Watering Food Photography Pada Postingan Instagram @Ayambakarmertua_Official Terhadap Minat Beli Konsumen - Lathyfah Lathyfah; Jupriani Jupriani (Jurnal Kajian dan Penelitian Umum, 2023)
The following research was conducted with the aim of knowing the effect of applying one of the food photography trends, namely mouth watering food photography by the Instagram account @ayambakarmertua_official in its posts on consumer buying interest. Researchers used quantitative methods with Likert scale measurements. The data source is primary data which is obtained directly based on respondents from a questionnaire for tools in obtaining data. The simple random sampling method was used by researchers for sampling with a total of 100 respondents based on the Lemeshow formula. From this study it was concluded that promotional media can influence consumer buying interest through the use of Mouth Watering Food Photography by the Instagram account @Ayambakarmertua_Official.